NIR Triggered Bionic Bilayer Membrane-Encapsulated Nanoparticles for Synergistic Photodynamic, Photothermal and Chemotherapy of Cervical Cancer - Ding J; Zhang X; Guo L; Xiong J; Zhang C; Du Z; Zhu L; Alifu N; Dong B (International Journal of Nanomedicine)
Jiayi Ding,1 Xueliang Zhang,2 Le Guo,1 Jiabao Xiong,3 Chi Zhang,1 Zhong Du,3 Lijun Zhu,3 Nuernisha Alifu,1– 3 Biao Dong2,4 1Institute of Public Health, Xinjiang Medical University, Urumqi, 830011, People’s Republic of China; 2State Key Laboratory of Pathogenesis Prevention and Treatment of High Incidence Diseases in Central Asia, School of Medical Engineering and Technology Xinjiang Medical University, Urumqi, 830011, People’s Republic of China; 3Second Clinical Medical College, Xinjiang Medical University, Urumqi, 830011, People’s Republic of China; 4State Key Laboratory on Integrated Optoelectronics, College of Electronic Science and Engineering, Jilin University, Changchun, 130012, People’s Republic of ChinaCorrespondence: Nuernisha Alifu, State Key Laboratory of Pathogenesis Prevention and Treatment of High Incidence Diseases in Central Asia, School of Medical Engineering and Technology Xinjiang Medical University, Urumqi, 830011, People’s Republic of China, Tel +86-18799167931, Email nens_xjmu@126.com Biao Dong, State Key Laboratory on Integrated Optoelectronics, College of Electronic Science and Engineering, Jilin University, Changchun, 130012, People’s Republic of China, Tel +86-13504329842, Email dongb@jlu.edu.cnPurpose: A synergistic treatment strategy of phototherapy and chemotherapy has been shown to improve efficacy and offer unique advantages over monotherapy. The purpose of this study is to explore a new nanocarrier system with liposome as the inner membrane and erythrocyte membrane as the outer membrane, which aims to realize the leak-free load of phototherapy drug indocyanine green (ICG) and chemotherapy drug doxorubicin (DOX), prolong the circulation time in vivo and improve the therapeutic effect.Patients and Methods: In this study, bilayer membrane-loaded ICG and DOX nanoparticles (RBC@ICG-DOX NPs) were prepared and characterized. For in vitro analysis, the biocompatibility and tumor inhibition properties of the nanoparticles were evaluated. For in vivo analysis, the antitumor properties of the nanoparticles were explored in a mouse subcutaneous tumor model.Results: RBC@ICG-DOX NPs were successfully prepared with strong safety and good blood compatibility, which can effectively reduce drug leakage and prolong drug circulation time in the body. In vitro performance evaluation showed that RBC@ICG-DOX NPs obtained excellent photothermal conversion ability and well reactive oxygen generation performance under near-infrared laser irradiation. Both in vitro and in vivo experiments showed well phototherapy-chemotherapy effect of RBC@ICG-DOX NPs with low toxic side effects.Conclusion: Drug delivery, imaging and tumor synergies were accomplished through combinatorial strategies as well as bilayer membrane encapsulation, opening up a new platform for the design of future tumor combination therapies.Keywords: erythrocyte membrane modification, indocyanine green, adriamycin, combination therapy, cervical cancer